Memory Scrapers: Readymade Concepts and Techniques as Reflected in Collecting and Recycling Patinated Lower Palaeolithic Items at Qesem Cave, Israel. Issue 2 (May 2021) - Efrati, Bar
Abstract : This paper argues that certain early Palaeolithic artefacts can be viewed as reflecting Readymade concepts and techniques from the world of modern art. I will focus on presenting a theoretical framework for this claim as well as a case study from Late Lower Palaeolithic Qesem Cave, Israel (420, 000–200, 000 bp ). The case study is based on the 'double patina' phenomenon (old tools that became patinated by exposure to the elements and were then shaped again). These items, characterized by outstanding colours and textures, were produced following Readymade concepts and techniques applied in the production of tools that are both functional and mnemonic. I suggest that these items acted as mnemonic memory tools that reconnected their users to ancestral (human and non-human) beings as well as to familiar experiences, events, and places.